Association between single moderate to severe traumatic brain injury and long-term tauopathy in humans and preclinical animal models: a systematic narrative review of the literature - Ariel Walker; Ben Chapin; Jose Abisambra; Steven T. DeKosky (Acta Neuropathologica Communications, 2022)
Abstract Background The initiation, anatomic pattern, and extent of tau spread in traumatic brain injury (TBI), and the mechanism by which TBI leads to long-term tau pathology, remain controversial. Some studies suggest that moderate to severe TBI is sufficient to promote tau pathology; however, others suggest that it is simply a consequence of aging. We therefore conducted a systematic narrative review of the literature addressing whether a single moderate to severe head injury leads to long-term development of tauopathy in both humans and animal models. Methods Studies considered for inclusion in this review assessed a single moderate to severe TBI, assessed tau pathology at long-term timepoints post-injury, comprised experimental or observational studies, and were peer-reviewed and published in English. Databases searched included: PUBMED, NCBI-PMC, EMBASE, Web of Science, Academic Search Premiere, and APA Psychnet. Search results were uploaded to Covidence®, duplicates were removed, and articles underwent an abstract and full-text screening process. Data were then extracted and articles assessed for risk of bias. Findings Of 4,150 studies screened, 26 were eligible for inclusion, of which 17 were human studies, 8 were preclinical animal studies, and 1 included both human and preclinical animal studies. Most studies had low to moderate risk of bias. Most human and animal studies (n = 12 and 9, respectively) suggested that a single moderate to severe TBI resulted in greater development of long-term tauopathy compared to no history of head injury. This conclusion should be interpreted with caution, however, due to several limitations: small sample sizes; inconsistencies in controlling for confounding factors that may have affected tau pathology (e.g., family history of dementia or neurological illnesses, apolipoprotein E genotype, etc.), inclusion of mostly males, and variation in reporting injury parameters. Interpretation Results indicate that a single moderate to severe TBI leads to greater chronic development of tauopathy compared to no history of head injury. This implies that tau pathology induced may not be transient, but can progressively develop over time in both humans and animal models. Targeting these tau changes for therapeutic intervention should be further explored to elucidate if disease progression can be reversed or mitigated.